Association between glycemic status and thyroid dysfunction in patients with type 2 diabetes mellitus - Ogbonna SU (Dove Medical Press, 2019)
SU Ogbonna,1 IU Ezeani,1 CI Okafor,2 S Chinenye31Department of Internal Medicine, Federal Medical Center, Umuahia, Abia State, Nigeria; 2Department of Internal Medicine, University of Nigeria Teaching Hospital, Enugu, Enugu State, Nigeria; 3Department of Internal Medicine, University of Port Harcourt Teaching Hospital, Port Harcourt, Rivers State, NigeriaBackground: Thyroid dysfunction has been widely reported to be more common in patients with type 2 diabetes mellitus (T2DM) in various parts of the world; however, there is paucity of data on this in our environment.Objective: The aim of this study was to determine the possible relationship between glycemic status and thyroid dysfunction.Methodology: A total of 354 T2DM patients and 118 non-diabetic persons (controls) were recruited for the study. A pretested questionnaire was filled for each subject after due explanations. Their blood samples were tested for HbA1c, fT3, fT4, and TSH. Information retrieved from patient’s medical records included age at diagnosis of diabetes (DM) and duration of DM. Testing statistics done included Student’s t-test, chi square test, and regression analysis. P-value of less than 0.05 was taken to be statistically significant.Results: The results show that 43.5% and 37.3% of T2DM and control subjects, respectively, were males. Mean HbA1c was significantly higher in T2DM patients than in the controls (7.8±2.0% vs 5.8±1.2%, p=0.001), while mean fT3 was significantly lower in T2DM patients than in the controls (2.3±1.5 pg/mL vs 2.7±2.2 pg/mL, p=0.03). Mean HbA1c was significantly higher in T2DM patients with thyroid dysfunction compared to their euthyroid counterparts (8.1±1.9% vs 5.1±1.2%, p=0.001). HbA1c had a positive linear relationship with the presence of thyroid dysfunction (regression coefficient=1.89, p=0.001).Conclusion: There was a positive linear relationship between HbA1c and the presence of thyroid dysfunction in the T2DM patients in this study. There was an inverse relationship between HbA1c and serum fT3.Keywords: thyroid dysfunction, type 2 diabetes mellitus, hypothyroidism, South East Nigeria, relationship, glycemic status